Traduction commentée de textes de l'émir Moustapha Chéhabi. - Stephan, Romancia. (University of Ottawa (Canada), 1996)
The writings of Moustapha Chehabi (best known as author of the Dictionnaire francais-arabe des termes agricoles and of a book about Arabic scientific terminology, Al-mustalahat al-ilmiyyat fi al-lught al-arabiyyat fi al-qadim wal-hadi th) illustrate the continuing influence of the Arab lexicographic tradition, and the spirit of the nahpdat (Arab Awakening), as well as major contemporary problems facing the Arabic language. As witness to the opening of the Middle-East to Western culture following centuries of lethargy, Chehabi succeeded in making use of the linguistic achievement of the Arabs of the classical era in order to develop methods which are adapted to the new needs of Arabic technical and scientific terminology, especially in the fields of agriculture and botany. Thanks to his perceptiveness, he was able to address major issues of contemporary Arabic: the inadequacy of existing Arabic dictionaries, the need for a dynamic methodology of neologizing which is also respectful of the particular characteristics of Arabic, and the urgent need for Arabic terminology unification. The thesis includes a historical background, a biography of Moustapha Chehabi and three annotated and commented translations of excerpts from his works, as well as a bibliography of his publications and a biographical lexicon of lexicographers and others who are mentioned by Chehabi or in the commentary.
Keywords: Language, Linguistics.